RETRACTED: Is the interaction of commercial regulation with foreign direct investment a source of Heaven or EKC hypothesis? An empirical investigation of the BRICS region - Wu, Chenmu; Zhou, Xiaoming; Ali, Muhammad (Frontiers in Environmental Science, 2022)
It is generally agreed that the quality of institutions, the amount of energy consumed, and foreign direct investment are among the essential factors in sustainable development. On the other hand, these aspects are just as critical as the others when determining what causes environmental deterioration and how the climate changes globally. This research used the dataset of the BRICS countries, which are classified as emerging nations, intending to determine the nature of the relationship between foreign direct investment and institutional quality in terms of an interaction term, in addition to other independent variables and environmental quality. The objective of this study was to determine whether or not a Pollution Heaven or Environmental Kuznets curve (EKC) exists in the BRICS countries. To accomplish this objective, the Pooled Mean Group (PMG) technique of econometrics was utilized to estimate a 21-year dataset between 2000 and 2020. The Pollution Heaven theory was shown to be true after empirical research was conducted on the BRICS economies. In these economies, this finding verified the expansion of foreign direct investment and the proliferation of business rules were sources of environmental degradation. In addition, no evidence was discovered to support the presence of the EKC theory in any of the BRICS countries or areas. Based on these empirical outcomes, this research suggested that the introduction of appropriate commercial laws is required to translate the benefits of foreign direct investment into environmentally sustainable development.